2023
DOI: 10.1007/s44197-023-00090-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Breakthrough Infection Among Vaccinated Population in the United Arab Emirates

Abstract: Background Despite significant efforts to contain the Coronavirus Disease 2019 (COVID-19) pandemic through mass vaccination, numerous nations throughout the world have recorded breakout infections. The incidence and severity of COVID-19 breakthrough infections in the United Arab Emirates (UAE) remain unknown despite extensive COVID-19 vaccine coverage. The goal of this research is to establish the characteristics of COVID-19 breakthrough infections in the UAE’s vaccinated population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…In contrast to our findings regarding older individuals, multiple studies have identified younger age as a risk factor for COVID-19 breakthrough infection [14,25,34] . It's important to note that these studies varied in design, cohort size, and follow-up duration, which may have influenced their ability to capture current evolving trends.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings regarding older individuals, multiple studies have identified younger age as a risk factor for COVID-19 breakthrough infection [14,25,34] . It's important to note that these studies varied in design, cohort size, and follow-up duration, which may have influenced their ability to capture current evolving trends.…”
Section: Discussioncontrasting
confidence: 99%
“…1 n (%); Median (IQR) Of the total cohort, 7,904 (5.9%) tested positive for SARS-Cov-2 infection by PCR during the study period in a median (IQR) of 135(34, 196) days. The infections occurred in a median (IQR) of 196 (115, 260) days after a booster dose of vaccine.…”
mentioning
confidence: 99%
“…Graphic design is commonly perceived as a visual method of communication employed to address matters requiring visual elements or convey information via pictorial symbols. According to Dash et al (2023), it is concurred that the perspective presented here is valid, as they contend that everyday objects can be seen as graphic designs based on their inherent visual attributes.…”
Section: Art In Graphic Designmentioning
confidence: 84%
“…These endeavors have garnered significant global recognition and have proven lucrative in attracting international attention thereby increasing investment. In the perception of Dash et al (2023), Dubai's transformation to a global economic hub is a noteworthy example of the strategic utilization of visual communication to foster and drive economic development. Moreover, the media of the United Arab Emirates plays a significant role in advancing its diplomatic endeavors by effectively projecting its values and objectives on the global stage.…”
Section: Art In Graphic Designmentioning
confidence: 99%
“…Such long follow-up duration was facilitated by the integrated EMR system and the Abu Dhabi COVID-19 vaccination strategy. The population of Abu Dhabi was more than 97.97% vaccinated for COVID-19 (15) and all vaccination visits required comprehensive chronic disease history and a physical examination, including BMI and blood pressure and sometimes repetition of some laboratory tests such as HA1C and kidney function. Only 18.4% of participants had their last (EMR) visit in 2019 or earlier.…”
Section: Resultsmentioning
confidence: 99%